The Urgency of Implementing a Core Tax Administration System in Tax Law Reform in the Fintech Era - Hary Kesowo Wibowo; Anto Kustanto; Ainul Masruroh (UNISSULA, 2026)
The rapid expansion of Financial Technology (FinTech) has transformed digital economic transactions and created challenges for tax administration, requiring reforms that ensure legal certainty, effective supervision, and equitable tax collection. This study examines the legal urgency of implementing the Core Tax Administration System (CTAS) as part of Indonesia’s tax law reform in the FinTech era. Using a qualitative descriptive design with a normative legal approach, the research analyzes Law Number 6 of 1983 as amended by Law Number 7 of 2021 on the Harmonization of Tax Regulations, Government Regulation Number 55 of 2022, policy documents, institutional reports, and relevant legal literature. The findings identify three legal urgencies. First, tax regulations require reconstruction to support an integrated digital administration system that provides legal certainty and accommodates technological developments. Second, CTAS strengthens tax collection by integrating taxpayer data, improving compliance, increasing administrative efficiency, and reducing tax avoidance. Third, modernization of tax administration promotes tax justice through transparent, accountable, and proportional tax obligations across conventional and digital sectors. The study concludes that successful CTAS implementation requires harmonization between tax regulations, digital governance, and personal data protection to establish an adaptive and equitable tax administration system supporting sustainable fiscal governance.